2007
DOI: 10.1088/0031-9155/53/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MLC leaf position errors on simple and complex IMRT plans for head and neck cancer

Abstract: The dosimetric impact of random and systematic multi-leaf collimator (MLC) leaf position errors is relatively unknown for head and neck intensity-modulated radiotherapy (IMRT) patients. In this report we studied 17 head and neck IMRT patients, including 12 treated with simple plans (<50 segments) and 5 treated with complex plans (>100 segments). Random errors (-2 to +2 mm) and systematic errors (+/-0.5 mm and +/-1 mm) in MLC leaf positions were introduced into the clinical plans and the resultant dose distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 15 publications
2
86
1
6
Order By: Relevance
“…2a), data delivery analysis proves that for 95% of gaps smaller than 10 mm, the random DG error is less than 0.7 mm. Based on these findings and data on delivery error simulations [7,10,16,30], we may conclude that MLC delivery errors have reduced effects on the patient dose distributions: in any case, Eclipse plan solutions with a reduced number of small gaps are desirable. This analysis underlines that MLC errors were reproducible over the whole investigation period regardless of the dose rate and gantry speed.…”
Section: Discussionmentioning
confidence: 86%
“…2a), data delivery analysis proves that for 95% of gaps smaller than 10 mm, the random DG error is less than 0.7 mm. Based on these findings and data on delivery error simulations [7,10,16,30], we may conclude that MLC delivery errors have reduced effects on the patient dose distributions: in any case, Eclipse plan solutions with a reduced number of small gaps are desirable. This analysis underlines that MLC errors were reproducible over the whole investigation period regardless of the dose rate and gantry speed.…”
Section: Discussionmentioning
confidence: 86%
“…The shift for the counterclockwise rotation is applied accordingly. For IMRT random leaf errors up to 2 mm were found to have little dosimetric effects 21,22 and initial tests with random leaf errors suggested the same outcome for Rapidarc treatment plans. The modifications representing conceivable worst case scenarios are summarized in Table I.…”
Section: Iid Rapidarc Treatment Plan Modificationsmentioning
confidence: 87%
“…In a study that proposed a Monte Carlo based IMRT dose verification method, Luo et al 34 found that an average MLC leaf positional error of 0.2 mm can result in a target dose error of about 1.0%. Mu et al 35 studied the impact of random and systematic MLC leaf position errors for head and neck IMRT patients. They found that the dosimetric effect was insignificant for random MLC leaf position errors up to 2 mm, but for a 1 mm systematic error, the average changes in D 95% were 4% in simple plans versus 8% in complex plans with notable differences also seen in spinal cord, brainstem, and parotid glands.…”
Section: Introductionmentioning
confidence: 99%